The effects of mountain bike suspension systems on energy expenditure, physical exertion, and time trial performance during mountain bicycling - Seifert, J. G.; Luetkemeier, M. J.; Spencer, M. K.; Miller, D.; Burke, E. R. (International Journal of Sports Medicine, 1997)
The purpose of this 3-Phase study was to investigate the effects of suspension systems on muscular stress, energy expenditure, and time trial performance during mountain biking. Three suspension systems were tested, a rigid frame bike (RIG), a suspension fork bike (FS), and a front and rear suspension bike (FSR). Phase I and II consisted of cycling at 16.1 km.hr-1 over a flat, bumpy course for 63 min. Phase III consisted of ascending (ATT), descending (DTT), and cross country (XTT) time trials. Phase I assessed muscular stress by 24 h change in CK, Phase II assessed HR, VO2, VE, and Phase III assessed performance responses to the suspension systems. The 24 hr change in CK was greater for RIG than FS and FSR (+91.9 +/- 79.5 IU vs +8.6 +/- 17.5 IU and +9.7 +/- 21.8 IU). Mean HR was greater for RIG than FS and FSR (153.7 +/- 15.6 bpm vs 146.7 +/- 15.4 bpm, 146.3 +/- 16.2 bpm). Subjects rode significantly faster on FS than FSR and RIG during the XTT (30.9 +/- 2.0 min vs 32.3 +/- 3.6 min, 32.3 +/- 3.2 min). Subjects RPE was lower for FSR than FS and RIG, however, no differences were observed for VO2, VE, ATT, or DTT. Cyclists incurred less muscular stress, indicated by CK and HR, when riding the FS and FSR. Although the FS and FSR weigh from 0.7 to 2.2 kg more than RIG, no differences were observed for energy expenditure and that riding the FS in a XTT resulted in a faster finishing time than FSR or RIG.